We Jews and Blacks : memoir with poems - Barnstone, Willis, 1927- (Indiana University Press, 2004)
Willis Barnstone's third book of memoirs begins with his childhood and ends with his brother's death in 1987. A central theme is labels - names, ethnicities, all distinctions that cause suspicion, anger, and destruction. Barnstone speaks as a Jew who has from early in his life shared parallel experiences with African Americans. He dwells on his own experience of "passing", already present in the name Barnstone, a name changed before his birth to conceal - or not to advertise - that he was a Jew, which might affect admission to private schools and college, his integration into society, and his